Cadmium-Induced Oxidative Stress: Focus on the Central Nervous System - Jacopo J. V. Branca; Claudia Fiorillo; Donatello Carrino; Ferdinando Paternostro; Niccolò Taddei; Massimo Gulisano; Alessandra Pacini; Matteo Becatti (MDPI AG, 2020)
Cadmium (Cd), a category I human carcinogen, is a well-known widespread environmental pollutant. Chronic Cd exposure affects different organs and tissues, such as the central nervous system (CNS), and its deleterious effects can be linked to indirect reactive oxygen species (ROS) generation. Since Cd is predominantly present in +2 oxidation state, it can interplay with a plethora of channels and transporters in the cell membrane surface in order to enter the cells. Mitochondrial dysfunction, ROS production, glutathione depletion and lipid peroxidation are reviewed in order to better characterize the Cd-elicited molecular pathways. Furthermore, Cd effects on different CNS cell types have been highlighted to better elucidate its role in neurodegenerative disorders. Indeed, Cd can increase blood-brain barrier (BBB) permeability and promotes Cd entry that, in turn, stimulates pericytes in maintaining the BBB open. Once inside the CNS, Cd acts on glial cells (astrocytes, microglia, oligodendrocytes) triggering a pro-inflammatory cascade that accounts for the Cd deleterious effects and neurons inducing the destruction of synaptic branches.